Analisis Kualitas Butir Soal Asesmen Sumatif Akhir Semester Gasal Matematika Kelas IV Sekolah Dasar: Penelitian - Priska Amanda; Bistari; Hery Kresnadi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to describe the quality of the multiple-choice items in the odd-semester summative assessment of mathematics for Grade IV students at SD Negeri 39 Pontianak Kota in the 2024/2025 academic year, in terms of validity, reliability, difficulty level, and discriminating power. The research employed a descriptive method with a quantitative approach, supported by Microsoft Excel. The subjects of this study were the Grade IV mathematics summative assessment items. Data were collected through documentation techniques to obtain the test items and the answer recapitulation of Grade IV-A students. The analysis results showed that 11 items (44%) were valid, with a high reliability coefficient (0.70). Regarding the level of difficulty, 12 items were easy, 10 were moderate, and 3 were difficult. In terms of discriminating power, 1 item was categorized as very good, 6 as good, 5 as fair, 8 as poor, and 5 as very poor. Overall, 8 items (32%) were considered good and suitable for reuse, while 17 items (68%) needed revision or replacement as they did not yet meet the criteria for high-quality test items.